Implementation of Good Corporate Governance to Improve the Quality of Human Resources in Village-Owned Enterprises (BUMDes) - Meida Rachmawati (PT Publikasiku Academic Solution, 2024)
The implementation of Good Corporate Governance (GCG) in improving the quality of Human Resources in Village-Owned Enterprises (BUMDes) is an important effort to strengthen organizational integrity, accountability, and performance at the local level. Although faced with constraints such as limited resources and resistance to change, effective GCG implementation can improve the transparency, responsibility, and independence of BUMDes. Strategies such as establishing a clear code of conduct, regular training, and building an independent oversight mechanism are necessary to overcome such obstacles. Successful implementation of GCG can provide great benefits in improving the quality of human resources and performance of BUMDes, and contribute positively to the development and welfare of rural communities. Qualitative research methods will be used to understand stakeholders' experiences, perceptions, and attitudes regarding the implementation of GCG in improving human resources in BUMDes.